2014
DOI: 10.1111/jcmm.12288
|View full text |Cite
|
Sign up to set email alerts
|

let‐7e replacement yields potent anti‐arrhythmic efficacy via targeting beta 1‐adrenergic receptor in rat heart

Abstract: Beta-adrenoceptor (β-AR) exerts critical regulation of cardiac function. MicroRNAs (miRNAs) are potentially involved in a variety of biological and pathological processes. This study aimed to investigate the role of miRNA let-7e in the up-regulation of β1-AR and arrhythmogenesis in acute myocardial infarction (AMI) in rats. β1-AR expression was significantly up-regulated and let-7a, c, d, e and i were markedly down-regulated in the infarcted heart after 6 and 24 hrs myocardial infarction. Forced expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…miR profiling by next-generation sequencing revealed 35 miRs to be altered by endurance training in the sinus node (Figure 2 E). Several of these miRs have previously been shown to exert regulatory effects in the heart: miR-486-3p, upregulated in the sinus node of the trained mice (Figure 2 E and 2 F), has previously been shown to be upregulated in the hearts of swim-trained mice and involved in the antifibrotic effects of exercise 37 ; Let-7e, upregulated in the sinus node of the trained mice (Figure 2 E and 2 F), has previously been shown to have an antiarrhythmic effect mediated via a downregulation of the β1 adrenergic receptor in myocardial infarction rats 38 ; finally, miR-10b-5p, downregulated in the sinus node of the trained mice (Figure 2 E and 2 F), has previously been shown to regulate the key cardiac transcription factor Tbx5, known to be involved with the cardiac conduction system. 39 Previously, the plasma level of miR-423-5p has been reported to be elevated in heart failure, acute myocardial infarction, stable coronary artery disease, and patients undergoing cardiac surgery.…”
Section: Discussionmentioning
confidence: 93%
“…miR profiling by next-generation sequencing revealed 35 miRs to be altered by endurance training in the sinus node (Figure 2 E). Several of these miRs have previously been shown to exert regulatory effects in the heart: miR-486-3p, upregulated in the sinus node of the trained mice (Figure 2 E and 2 F), has previously been shown to be upregulated in the hearts of swim-trained mice and involved in the antifibrotic effects of exercise 37 ; Let-7e, upregulated in the sinus node of the trained mice (Figure 2 E and 2 F), has previously been shown to have an antiarrhythmic effect mediated via a downregulation of the β1 adrenergic receptor in myocardial infarction rats 38 ; finally, miR-10b-5p, downregulated in the sinus node of the trained mice (Figure 2 E and 2 F), has previously been shown to regulate the key cardiac transcription factor Tbx5, known to be involved with the cardiac conduction system. 39 Previously, the plasma level of miR-423-5p has been reported to be elevated in heart failure, acute myocardial infarction, stable coronary artery disease, and patients undergoing cardiac surgery.…”
Section: Discussionmentioning
confidence: 93%
“…Let-7 has been demonstrated enriched in the mouse heart, and upregulated in the heart failure 31. Li et al has demonstrated that let-7 is downregulated in the acute myocardial infarction and contributes to the anti-arrhythmic efficacy 19. Sayed's result showed that let-7b and let-7c are upregulated, but let-7d downregulated in the TAC mice 32.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that miRNAs play a critical role in regulation of cardiac developmental and cardiovascular diseases 13-15. It has been reported that let-7 plays a crucial role in multiple biologic functions, including tumor suppression 16, 17, axon regeneration 18, arrhythmia inhibition 19, and cardiac fibrosis and apoptosis reduction 20. A study by Gray et al showed that upregulation of let-7 may be involved in regulation of cardiac hypertrophy process in rats 21.…”
Section: Introductionmentioning
confidence: 99%
“…Possibilities include sex differences in cardiac adrenergic activity with age, the effects of sex hormones directly or through an interaction with adrenergic activity, 39 thyroid hormone effects, 12 or differential regulation by microRNAs. 40 In addition to being a biosensor of cardiac adrenergic activity, the decline in β 1 -AR density may be an adaptive change that protects the heart from adverse adrenergic signaling. 2 The higher expression of β 1 -ARs in women in the youngest age group could provide a means of augmenting cardiac output in stressful situations, such as pregnancy and childbirth, but could also predispose to cardiac damage, for example, as seen in peripartum cardiomyopathy.…”
Section: Figurementioning
confidence: 99%